2008
DOI: 10.1128/jvi.01374-07
|View full text |Cite
|
Sign up to set email alerts
|

Amiloride Derivatives Inhibit Coxsackievirus B3 RNA Replication

Abstract: Amiloride derivatives are known blockers of the cellular Na . Here, we demonstrate that amiloride and EIPA strongly inhibit coxsackievirus B3 (CVB3) RNA replication and do not inhibit CVB3 release, in contrast to our previous findings on HRV2. Passaging of plasmid-derived CVB3 in the presence of amiloride generated mutant viruses with amino acid substitutions in position 299 or 372 of the CVB3 polymerase. Introduction of either of these mutations into the CVB3 plasmid produced resistance to amiloride and EIPA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 28 publications
(38 reference statements)
5
43
3
Order By: Relevance
“…EIPA had a stronger inhibitory effect than amiloride (Fig. 1B), consistent with its stronger effect on CVB3 replication in cell culture (11). S299T 3D pol was less susceptible to inhibition than WT 3D pol ( Fig.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…EIPA had a stronger inhibitory effect than amiloride (Fig. 1B), consistent with its stronger effect on CVB3 replication in cell culture (11). S299T 3D pol was less susceptible to inhibition than WT 3D pol ( Fig.…”
Section: Resultssupporting
confidence: 72%
“…Amiloride and its derivative 5-(N-ethyl-N-isopropyl)amiloride (EIPA) inhibit CVB3 propagation in cell culture by inhibiting viral genome replication (11). Two amino acid substitutions in 3D pol (S299T and A372V) confer partial resistance of the virus to the compounds, suggesting that amiloride analogues may act as inhibitors of CVB3 3D pol (11). Here we show that amiloride and EIPA inhibit VPg uridylylation and RNA elongation by CVB3 3D pol in vitro, acting as competitive inhibitors with respect to nucleoside triphosphates (NTPs) and Mg 2ϩ .…”
mentioning
confidence: 99%
“…EIPA was previously shown to inhibit propagation of human rhinovirus 2 and Coxsackie B3 virus in HeLa cells (59). In this study, EIPA failed to inhibit HEV71 infection.…”
Section: Discussionmentioning
confidence: 51%
“…The possibility that this drug affects entry can be excluded because immunofluorescence microscopy clearly showed that virus entered the cells in its presence. For coxsackievirus B3 and for HRV2, inhibition of RNA replication and of virus release, respectively, by amiloride has been suggested (12,18). Our data, rather, point to inhibition of RNA release into the cytosol, RNA translation, or even inhibition of polyprotein processing.…”
Section: Entry Of Hrv2mentioning
confidence: 51%
“…Viral replication is not required for this process because translation of the incoming RNA produces the proteinase 2A in sufficient amounts for cleavage of this cellular substrate (13). In this way, possible effects of the drugs on later steps, such as RNA synthesis and/or virus release (12,18), can be excluded. Furthermore, there is no need to maintain the cells in the presence of the drug for extended times, thus avoiding interference by cytotoxic effects.…”
Section: Discussionmentioning
confidence: 99%